Effect of grinding on the nutritive value of grain sorghums for fattening steer calves. - Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
Livestock feeders have often called attention to the large amount of sorghum grains passing through cattle when the whole grain is fed. Small hard grain, when not broken by chewing, seems to escape digestion altogether. The question, therefore, has arisen as to the best method of feeding grain sorghums for the most efficient utilization by fattening cattle.
Keywords: Beef; Nutrition; Grain sorghum; Gain